New approaches to image processing based failure analysis of nano-scale ULSI devices - Zalevsky, Zeev.; Livshits, Pavel; Gur, Eran.; ScienceDirect eBooks (Oxford : William Andrew, 2014)
New Approaches to Image Processing Based Failure Analysis of Nano-Scale ULSI Devices introduces the reader to transmission and scanning microscope image processing for metal and non-metallic microstructures. Engineers and scientists face the pressing problem in ULSI development and quality assurance: microscopy methods can't keep pace with the continuous shrinking of feature size in microelectronics. Nanometer scale sizes are below the resolution of light, and imaging these features is nearly impossible even with electron microscopes, due to image noise.
Machine generated contents note: 1. Introduction -- 1.1. Basics of Image Processing -- 1.2. The Problems of Shrinking Feature Size in ULSI Development and Failure Analysis -- 1.3. High Resolution Imaging of Structures -- 1.4. Fabrication Techniques in ULSI Industry -- References -- 2. New Image Processing Methods for Advanced Metallization in Micro- and Nano-Electronics -- 2.1. Characteristics of Metal Ultrathin Films' Microstructures -- 2.2. Increased Productivity by Obviating Steps of Selection of Measurement Conditions -- 2.3. Demonstration of Method Capabilities -- References -- 3. New Super Resolving Techniques and Methods for Microelectronics -- 3.1. The Basics of Super Resolution -- 3.2. Super-Resolution Imaging for Improved Failure Analysis -- 3.3. Usage of Radon Transform for Improved Failure Analysis.
Print version record.
Includes bibliographical references.
Elsevier
Keywords: Integrated circuits -- Ultra large scale integration -- Testing; Nanoelectronics; Microelectronics; TECHNOLOGY & ENGINEERING -- Mechanical; Integrated circuits -- Ultra large scale integration -- Testing; Microelectronics; Nanoelectronics; Electronic books